Hétéroptères phytophages et prédateurs d'Afrique de l'Ouest - Poutouli, Wiyao; Silvie, Pierre; Aberlenc, Henri-Pierre (éditions Quae, 2011)
"Specific studies on the biodiversity or the implementation of the concept of integrated farming imply the need to know how to identify the insect pests or natural enemies. In some countries, growing transgenic, caterpillar-resistant plants, like cotton or corn, has reduced the use of insecticide treatments to control these pests. Some families of bugs like the Pentatomidae and the Miridae have thus become major pests. It is therefore important to improve our understanding of these pests sometimes considered as secondary. People working in the field will find in this book a brief description of the main species of phytophage and predatory bugs found in West Africa, principally in cotton, corn, cowpea (Vigna unguiculata), soy bean and sorghum."